2016
DOI: 10.2486/indhealth.2015-0248
|View full text |Cite
|
Sign up to set email alerts
|

Hematocrit levels as cardiovascular risk among taxi drivers in Bangkok, Thailand

Abstract: In Thailand, taxi drivers employed in the informal sector often experience hazardous working conditions. Previous studies revealed that elevated Hematocrit (HCT) is a predictor of cardiovascular disease (CVD) risk. This study assessed factors associated with HCT in taxi drivers to predict their occupational CVD risk factors. A cross-sectional study was conducted on 298 male taxi drivers who joined a health check-up campaign in Bangkok, Thailand. HCT and body mass index were retrieved from participant health ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Of the 36 micro-level research studies, the majority were studies conducted in LMICs (29, 80.6%). Diverse types of informal workers were studied in LMICs, including waste workers [ 16 21 ], trash pickers [ 22 ], clay artisans [ 23 ], taxi drivers [ 24 ], artisanal and small-scale gold miners [ 25 ], informal commerce workers [ 26 ], female beer promoters [ 27 ], domestic workers [ 28 ], informal fisheries [ 29 ], and informal workers in the construction and manufacturing industry [ 30 37 ]. The remaining micro-level studies were conducted in LMICs [ 38 43 ] and HIC contexts [ 9 ], rather than focusing on a specific type of informal workers, and analyzed survey data or injury reports to examine the difference in health outcomes between workers in informal and formal employment.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 36 micro-level research studies, the majority were studies conducted in LMICs (29, 80.6%). Diverse types of informal workers were studied in LMICs, including waste workers [ 16 21 ], trash pickers [ 22 ], clay artisans [ 23 ], taxi drivers [ 24 ], artisanal and small-scale gold miners [ 25 ], informal commerce workers [ 26 ], female beer promoters [ 27 ], domestic workers [ 28 ], informal fisheries [ 29 ], and informal workers in the construction and manufacturing industry [ 30 37 ]. The remaining micro-level studies were conducted in LMICs [ 38 43 ] and HIC contexts [ 9 ], rather than focusing on a specific type of informal workers, and analyzed survey data or injury reports to examine the difference in health outcomes between workers in informal and formal employment.…”
Section: Resultsmentioning
confidence: 99%
“…The proportions of overweight and obesity among motorcycle taxi drivers in Hanoi were also lower than those among car taxi drivers in Thailand and Taiwan. It was reported that 53.9% of car taxi drivers in Thailand were obese [43], and 35% of car taxi drivers in Taiwan were overweight and 24% were obese [44]. This could be partly attributed to the higher prevalence of overweight and obesity among adults in Thailand and Taiwan when compared to Vietnam [42].…”
Section: Discussionmentioning
confidence: 99%
“…Considered Factors Hagl and Kouabenan [16] Staubach et al [17] Needs for advanced driver assistance system (ADAS) Li et al [18] Working hours/Time spent on personal affairs/Fatigue level Meng et al [15] Fatigue level Wang et al [9] Level of job satisfaction Wang et al [9] Ba et al [19] Frequency of safety education by the company Vahedi et al [20] Working hours per week/Level of living satisfaction/Age Ishimaru et al [21] Drinking frequency Bulduk et al [22] Usual fatigue level/Age Lim et al [23] Amount of sleeping time…”
Section: Literaturesmentioning
confidence: 99%